ANALISIS DANA SISA LEBIH PEMBIAYAAN ANGGARAN (SiLPA) DALAM PELAKSANAAN ANGGARAN PENDAPATAN DAN BELANJA NEGARA TAHUN ANGGARAN 2008-2010 - , Bekti Wicaksono, Sukmawati Sukamulja, Prof., Dr., M.M. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Implementation of deficit budget policy in the state budget must be covered by the financing. Condition of non-debt financing becomes more scarcely, making debt financing as the main source of financing. The fact indicates that at the end of the fiscal year 2008-2010, leaving the fund SiLPA. The existence of SiLPA funds in implementing of state budget indicates a problem in the management of state finances, especially the lack of coordination between cash and debt management. This study aims to examine and improve the financial management of government particularly the relationship between cash and debt management. This research was conducted in DJPB and DJPU, the Ministry of Finance, which has the main tasks and functions in cash and debt management. This research use descriptive research method. The study was conducted by analysis which focuses on the underlying motives of holding cash, namely (1) transactions motive, (2) precaution motive, and (3) speculation motive. This was done because SiLPA funds represent cash comes largely from the proceeds of debt. Furthermore, it is done an analysis of efficiency and effectiveness with the funds SiLPA and the presentation of the proposed model coordination between cash management with debt. The research concludes that funding for the transaction motive for showing the excess, for precaution motives show the level of accuracy in the planning of cash to the average is still below 95%, and for the speculative motive is still not done because it has not completed the legal rule. Also, found the fact that there has been conflict between the managers managing the debt as cash with the statement Pattanayak (2008). Directly, the existence of the state budget funds in implementing SiLPA current budget year will increase risk in debt management, particularly the refinancing risk and interest rates.